2009
DOI: 10.1074/jbc.m809551200
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Ron Kinase Inhibits Mutant Phosphatidylinositol 3-Kinase and Reduces Metastasis in Human Colon Carcinoma

Abstract: Abnormal accumulation and activation of receptor tyrosine kinase Ron (recepteur d'origine nantais) has been demonstrated in a variety of primary human cancers. We show that RNA interference-mediated knockdown of Ron kinase in a highly tumorigenic colon cancer cell line led to reduced proliferation as compared with the control cells. Decreased Ron expression sensitized HCT116 cells to growth factor deprivation stress-induced apoptosis as reflected by increased DNA fragmentation and caspase 3 activation. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 59 publications
1
94
0
Order By: Relevance
“…Inhibition of RON has implicated its signaling for PDAC cell growth and survival in preclinical studies (2)(3)(4)(5)(6)10). Various studies have shown that therapeutic antibodies and TKIs specific to RON inhibit tumor growth mediated by pancreatic, colon, and breast cancer cells in mouse tumor xenograft models (7,12,13,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of RON has implicated its signaling for PDAC cell growth and survival in preclinical studies (2)(3)(4)(5)(6)10). Various studies have shown that therapeutic antibodies and TKIs specific to RON inhibit tumor growth mediated by pancreatic, colon, and breast cancer cells in mouse tumor xenograft models (7,12,13,31).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that RON is overexpressed and activated in primary PDAC samples and established cell lines (1)(2)(3)(4)(5)(6). Here, we determined the therapeutic effect of BMS-777607 on RON signaling in L3.6pl cells and CSCs þ24/44/ESA .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in PIK3CA which encodes the p110α catalytic subunit of PI3K are observed in a large number of CRC patients and HCT116 which has H1076R gain of function mutation. It was observed that knockdown of RON kinases inhibits the activation of mutant PI3K and thereby the metastatic potential of orthotropically injected colon cancer cells [24]. RON siRNA inhibited signaling by β-catenin suggesting the regulation of this pathway by RON kinase [49,50].…”
Section: Ron Activated Signaling Pathwaysmentioning
confidence: 99%
“…Studies from our own laboratory and others have shown that RON contributes to the malignant and invasive phenotype of CRC [24]. RON has been shown to regulate several key processes in colon tumor progression and also plays active role in EMT which is analogous its role in embryonic development [25].…”
Section: Introductionmentioning
confidence: 99%